The early mother-to-child bond and its unique prospective contribution to child behavior evaluated by mothers and teachers - Fuchs, Anna; Möhler, Eva; Reck, Corinna; Resch, Franz; Kaess, Michael (Psychopathology, 2016)
Maternal bonding has been described as the quality of the affective tie from a mother to her infant. This early bond's mental components and its longitudinal impact on child outcome have been markedly understudied. Although most researchers assume impaired maternal bonding to have a negative impact on child development, there is a lack of prospective studies evaluating this hypothesis. Since maternal mental health problems may negatively affect both bonding quality and child development, it is still to be determined whether there is a unique contribution of bonding quality to child behavior problems over and above maternal psychopathology. We examined a community sample of 101 mother-child dyads at the child's age of 2 weeks (t1) and 6 weeks (t2), 4 months (t3), 14 months (t4), and 5.5 years (t5). Maternal bonding and psychopathology were assessed at time points t1-t4 using the Postpartum Bonding Questionnaire (PBQ-16) and the Symptom Checklist Revised (SCL 90-R). Child behavior problems were rated in a multi-informant design by mothers and teachers at t5 using the Strengths and Difficulties Questionnaire (SDQ). In the case of maternal judgment of child behavior problems, bonding at 14 months (t4) proved to be a significant predictor (β = 0.30; p = 0.011). Teacher-rated child behavior problems were significantly predicted by maternal bonding at 2 weeks (t1; β = 0.48; p = 0.025). Our results indicate a prospective influence of the early mother-infant bond on child development and underline the unique contribution of bonding quality to child behavior problems over and above the impact of maternal psychopathology in a community sample.